2018
DOI: 10.1017/ice.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Clostridium difficile Infection (CDI) Rates Using Real-Time Automated Clinical Criteria Verification to Enforce Appropriate Testing

Abstract: C. difficile PCR testing identifies both colonized and infected patients, making it critical to only test patients that meet clinical criteria for C. difficile infection (CDI). We implemented an automated order-entry protocol that reduced inappropriate testing by 64% and hospital-onset (HO) CDI Standardized Infection Ratio (SIR) from 1.62 to 0.82.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Previous studies have reported the impact of DSP on HO-CDI rates, but to our knowledge, ours is the first to link it to molecular epidemiology. 8,9 WGS has provided novel data on the transmission patterns for C. difficile, which is, in turn, prompting adjustments on appropriate diagnostic and infection prevention responses. A focused DSP, informed by WGS, allowed for the rapid translation of results from bench to bedside, and future studies will undoubtedly reveal continued expansion of this partnership.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the impact of DSP on HO-CDI rates, but to our knowledge, ours is the first to link it to molecular epidemiology. 8,9 WGS has provided novel data on the transmission patterns for C. difficile, which is, in turn, prompting adjustments on appropriate diagnostic and infection prevention responses. A focused DSP, informed by WGS, allowed for the rapid translation of results from bench to bedside, and future studies will undoubtedly reveal continued expansion of this partnership.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is not novel in its outcomes; other centers have also demonstrated reductions in C. difficile testing and HO-CDI rates with diagnostic stewardship processes. [11][12][13][14] However, we developed a novel model that was similarly effective and easily integrated into existing resources and infrastructure. Existing models described in the literature were not felt to be an appropriate fit for our institution for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…A final model required prior authorization from infectious diseases or gastroenterology physicians. 11 Given the patient load that such services carry at our institution, adding an additional responsibility was not considered feasible.…”
Section: Discussionmentioning
confidence: 99%
“…At least 1 participating Orange County ACH reported that a diagnostic stewardship intervention, not associated with the collaborative, reduced HO-CDI incidence within their hospital. 16 The SHIELD OC initiative, led by the University of California, Irvine, and LA BioMed at Harbor, University of California, Los Angeles, in partnership with Orange County Health Care Agency, CDPH and CDC, has enrolled 36 Orange County healthcare facilities in an intervention in which chlorhexidine is used to decolonize specific facility patient populations to prevent transmission of multidrug-resistant organisms across the Orange County healthcare network. 17,18 The intervention phase of SHIELD OC began in July 2017 and coincided with the final 6 months of the follow-up period in this analysis.…”
Section: Discussionmentioning
confidence: 99%